Электромагнитные флуктуации в спиральном волноводе с гиротропной средой - Якименко, И.П.; Назаренко, Л.А.; Шадрин, А.А. (Radiotekhnika, 1966)
Электромагнитные флуктуации в спиральном волноводе с гиротропной средой